Comparison of the antimicrobial effects of zinc titanium and aluminum doped copper oxide nanoparticles produced under the same conditions - Yilmaz, Mustafa; Aykut, Sehrazat Yaren; Erdim, Muhammed Kiyami; Bozdogan, Ayseguel Celik; Gur, Gunseli Kurt; Oruc, Cigdem (WILEY-V C H VERLAG GMBH, 2025)
The antibacterial nanoparticles have technological uses in many areas, from wall paint to clothing, from medicine to agriculture. Such copper oxide (CuO) nanoparticles can be easily produced by the sol-gel method. In this study, primarily pure CuO and CuO nanoparticles doped with 4%, 8%, 12%, and 16% zinc, titanium, and aluminum were produced by the sol-gel method. Field Emission Scanning Electron Microscopy (FESEM), Fourier transform infrared spectroscopy (FTIR) and x-ray diffraction (XRD) analyses of all produced nanoparticles were performed. The dimensions of pure CuO nanoparticles are approximately 50 nm, while the doped nanoparticles are approximately 80 nm. Bacterial cultivation was carried out using the nanoparticles that had been converted into tablets, with Escherichia coli and Agrobacterium tumefaciens as the test microorganisms. When disc diffusion test results were evaluated, it was generally observed that doping increased the antibacterial effect compared to pure CuO. The additives providing the antibacterial effect for E. coli caused the inhibition zones to grow at an average rate of Al (27%), Zn (15%), and TiO (6%), respectively. In A. tumefaciens bacteria, an increase was observed in the antibacterial effect inhibition zones with Al and Zn additives, while a decrease was observed with TiO additives. As a result, it was seen that CuO doping increased the antibacterial effect, and the best effect was Al doping. When all data were evaluated, the highest antibacterial effect was achieved with 8% Aluminum additive, resulting in a 34% increase in the inhibition diameter for E. coli and a 37% increase for A. tumefaciens.
Keywords: agrobacterium tumefaciens; aluminum doping; antimicrobial activities; CuO nanoparticles; Escherichia coli; titanium; zinc; SILVER NANOPARTICLES; CUO; NANOCOMPOSITE; BACTERIA; Chemistry